Perubahan Pola Permukiman Orang Laut Suku Duano - Ichwan Azhari; Onggal Sihite; Ida Liana Tanjung (Universitas Negeri Medan, 2018)
This paper examines changes in Orang Laut settlements in two villages namely Tanjung Solok Village and Jambi Province Fisheries Village. Changes occurred from settlements on boats in the sea to settlements inside houses in the village. The research method used is an ethnographic research method whose characteristics are